Finance And Other Services Sectors In Peninsular Malaysia, Sabah and Sarawak : Testing for Stochastic Convergence - Muzafar Shah Habibullah; M. T. Hirnissa; A. H. Baharom (Aceh International Journal of Social Science, 2012)
Abstract - In the last four decades, the financial services sector has becoming more important for the Malaysian economy. Despite gaining importance for enhancing economic growth, the contribution of the finance sector to the total services real Gross Domestic Product (GDP) has been ranked second in Peninsular Malaysia, third in Sabah and fourth in Sarawak. The purpose of the present paper is to determine whether the contribution of the financial services sector in the three regions in Malaysia, namely Peninsular Malaysia, Sabah and Sarawak show any distinct pattern. In the jargon of economic development literature, we seek to determine whether there is “convergence” or similarity in the patterns of the performance of the financial services sector among the three regions. Generally, our results suggest divergence of the finance sector and other sub-sector of the services among the three regions.